1986
DOI: 10.1128/aem.52.4.607-611.1986
|View full text |Cite
|
Sign up to set email alerts
|

Biodelignification of Lemon Grass and Citronella Bagasse by White-Rot Fungi

Abstract: Twelve white-rot fungi were grown in solid-state culture on lemon grass (Cymbopogon citratus) and citronella (Cymbopogon winterianus) bagasse. The two lignocellulosic substrates had 11% permanganate lignin and a holocellulose fraction of 58%. After 5 to 6 weeks at 20°C, nine fungi produced a solid residue from lemon grass with a higher in vitro dry matter enzyme digestibility than the original bagasse; seven did the same for citronella. The best fungus for both substrates was Bondarzewia berkeleyi; it increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 41 publications
(36 reference statements)
1
10
0
Order By: Relevance
“…1997), tree leaves (Osono 2007), and grass tissues (Abbott and Wicklow 1984; Wicklow et al. 1984; Rolz et al. 1986; Almendros et al.…”
Section: Introductionmentioning
confidence: 99%
“…1997), tree leaves (Osono 2007), and grass tissues (Abbott and Wicklow 1984; Wicklow et al. 1984; Rolz et al. 1986; Almendros et al.…”
Section: Introductionmentioning
confidence: 99%
“…Little attention has been paid to biodegradation of tannin-rich materials. White rot fungi are known to degrade lignin (Zadrazil 1980;Kamra and Zadrazil 1986;Rolz et al 1986;Kewalramani et al 1988;Kerem et al 1992). As lignins and tannins are structurally and biosynthetically related polymers whose monomer units are phenols, we studied the degradation of tannins in oak leaves using Sporotrichum pulverulentum, a white rot fungus.…”
mentioning
confidence: 99%
“…have been cultivated on lignocellulose with expectation of utilizing the metabolism of the microorganism to destruct the crystallinity of cellulose and remove lignin. However, most studies were based on laboratory scales and showed limited results [26][27][28][29].…”
Section: Biological Methodsmentioning
confidence: 99%